2017
DOI: 10.1002/pssb.201700480
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of n‐GaN Schottky Contacts With Wavy Surface Morphology Using Scanning Internal Photoemission Microscopy

Abstract: We characterized the effects of surface morphology on the electrical properties of n‐GaN drift‐layers by using scanning internal photoemission microscopy (SIPM). We grew 12‐μm‐thick low carrier concentration (approximately 1 × 1016 cm−3) n‐GaN layers with both flat and wavy surface morphologies on freestanding GaN substrates by metal organic chemical vapor deposition. In the SIPM results, the samples with flat surfaces exhibited a uniform photocurrent distribution independently of the carrier concentration. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 22 publications
(27 reference statements)
1
11
0
Order By: Relevance
“…It is considered that the sparse emission at avalanche breakdown reflected the internal compensation of carbon and nonuniformity of donor incorporated in bunched step edge. [30][31][32] In summary, we greatly reduced the leakage current and improved the breakdown voltage of a GaN p-n diode using a vertically and deeply etched mesa structure. We also succeeded in observing a stable nondestructive voltage breakdown and obtained evidence by evaluation of the temperature dependence that this phenomenon was an avalanche breakdown.…”
mentioning
confidence: 93%
“…It is considered that the sparse emission at avalanche breakdown reflected the internal compensation of carbon and nonuniformity of donor incorporated in bunched step edge. [30][31][32] In summary, we greatly reduced the leakage current and improved the breakdown voltage of a GaN p-n diode using a vertically and deeply etched mesa structure. We also succeeded in observing a stable nondestructive voltage breakdown and obtained evidence by evaluation of the temperature dependence that this phenomenon was an avalanche breakdown.…”
mentioning
confidence: 93%
“…14) The presence of irregular morphology, such as the macrosteps frequently observed in thick GaN drift layers grown homoepitaxially on GaN free-standing substrates, also complicates the situation, inducing inhomogeneous carrier concentrations across the electrode and wafers, as revealed by recent microscopic photoluminescence (PL), microscopic electroluminescence (EL), and photoemission microscopy observations. 15,16) This microscopic nonuniformity in the carrier concentration was tentatively attributed to off-angle-dependent incorporation of Mg or carbon in these works. Irrespective of the origin of the nonuniform carrier concentration, lower performance and yield were reported for vertical homoepitaxial GaN PNDs grown by MOCVD (MOCVD-PNDs) on a rough surface compared to those of diodes on a flat surface.…”
mentioning
confidence: 74%
“…We have reported that incorporated C atoms during the MOCVD growth affected carrier compensation when Si doping concentration was as low as low 10 16 cm −3 or below. 33) In addition, the amount of the C atoms incorporated depends on an off-angle of the GaN surface. 34) One possible explanation for the variations of the measured donor concentrations is by such compensation.…”
Section: Resultsmentioning
confidence: 99%